Perempuan kepala daerah: jati diri sebagai modal individual dan infrastruktur politiknya dalam tata pemerintahan daerah - Fajar Apriani (Publisia: Jurnal Ilmu Administrasi Publik, 2019)
This article describes a picture of the problems and achievements of women's leadership in the realization of gender justice in the regions and their supporting factors. With a locus of research on government at the executive level in Indonesia and objects of study on women Regional Head / Deputy Regional Head, this study produced findings that the profiles of women regional leaders have diverse socio-political backgrounds, individual capital and party bearers. Although there are currently many women leaders who become leaders at the executive level, they have not yet been fully born in the space of structural transformation and governance relations. So that decentralization and regional autonomy should not only serve as momentum marking changes in governance at the regional level, but rather become a structure of change itself, which opens opportunities for structural transformation and restructuring of power relations so that women's leadership becomes more meaningful in regional government. The emergence of women leaders in the regions is still inseparable from familial ties which have taken women hostage to past attachments while structurally hampering the movement of change itself.DOI:  https://doi.org/10.26905/pjiap.v4i2.3389